Mind the Gap? A Rural-Urban Comparison of Manufacturing Firms - Rijkers, Bob; Soderbom, Mans; Loening, Josef (2012)
This paper compares and contrasts the performance of rural and urban manufacturing firms in Ethiopia to assess the impact of market integration and the investment climate on firm performance. Rural firms are shown to operate in isolated markets, have poor access to infrastructure and a substantial degree of market power, whereas urban firms operate in better integrated and more competitive markets, where they have much better access to inputs. Fragmentation may also help explain why urban firms are much larger, much more capital intensive and why they produce much more output per worker. Capital intensity and labor productivity are strongly correlated with firm size. Manufacturing technology choice does not vary strongly across space and increasing returns to scale are modest at best, suggesting that rural-urban differences in output per worker are predominantly driven by differences in capital intensity and Total Factor Productivity (TFP). The average TFP of firms in rural towns is much higher than that of rural firms in remote areas, but small firms in rural towns are not significantly less productive than small firms in other urban areas. A key finding of the paper is that market fragmentation and investment climate constraints impair the growth of the rural non-farm sector. Whereas urban firms exhibit a healthy dynamism, rural firms are stagnant and lack incentives to invest. Paradoxically, limited local demand due to market fragmentation is the most pressing constraint for rural firms, even though they face more severe supply-side constraints than urban firms. Promoting market towns in Ethiopia might be an effective means of capitalizing on the gains from market integration.